1997
DOI: 10.1038/bjc.1997.385
|View full text |Cite
|
Sign up to set email alerts
|

Computerized detection of morphological changes to glioma cells during estramustine and ion-channel blocker perifusion

Abstract: Summary A perifusion technique for microscopy with computerized detection of early changes in cell morphology during continuous perifusion was used to show that the geometry of cultured glioma cells (MG-251) changes rapidly when they are exposed to estramustine phosphate (EMP). When the cells were exposed to 20 or 40 mg 1-' EMP, cell volume projected cell area (PCA) rapidly increased. When the Na+, K+-ATPase blocker ouabain (100 ,umol 1-') was added to the EMP (40 mg 1-') perifusion, the acute EMP response was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In previous reports we have shown that very early changes in cell size and shape correlated with the cytotoxicity to glioma cells of the anticancer drug estramustine phosphate (Engström et al 1991;Behnam-Motlagh et al 1997). The increase in cell volume indicated that estramustine phosphate caused a reduction of cellular ion efflux reflected in a decreased 86 Rb π influx with a total net accumulation of ions and water into the cell (Engström et al 1991).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous reports we have shown that very early changes in cell size and shape correlated with the cytotoxicity to glioma cells of the anticancer drug estramustine phosphate (Engström et al 1991;Behnam-Motlagh et al 1997). The increase in cell volume indicated that estramustine phosphate caused a reduction of cellular ion efflux reflected in a decreased 86 Rb π influx with a total net accumulation of ions and water into the cell (Engström et al 1991).…”
Section: Discussionmentioning
confidence: 85%
“…Thus, there exist a possibility of interactions between drugs that influence transmembrane fluxes of cations and anti-neoplastic drugs. The Na π , K π , 2Cl ª -cotransport inhibitors furosemide and bumetanide reduced the cytotoxicity of estramustine phosphate to pulmonary mesothelioma (P 31) cells (Sandström et al 1994), and also completely blocked estramustine phosphate-induced cell volume changes of glioma cells (Behnam-Motlagh et al 1997). Grankvist/klinkemi.umu.se). formed fibroblasts (Grankvist et al 1992).…”
mentioning
confidence: 99%
“…Changes in cell size and shape has been shown to correlate with EMP cytotoxicity to glioma cells (Engstrom et al 1991;Behnam-Motlagh et al 1997). At least three different potassium ion flux pathways seem to exist in the tumour cell line used (malignant glioma Mg251), i.e., Na + , K + , ATPase, Na + , K + , 2Cl --cotransport system, and K channels with high conductance (Sandstrom et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been used in previous reports regarding EMP cytotoxicity (Engstrom et al 1991;Behnam-Motlagh et al 1997;Behnam-Motlagh et al 2000). In short, we used a special type of microperifusion chamber consisting of glass slides forming a compartment in which cancer cells could be perifused.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation